Fetal muscle extract improves muscle function and performance in aged mice - Hiu Tung Jessica Lo; Hiu Tung Jessica Lo; Hiu Tung Jessica Lo; Tsz Lam Yiu; Tsz Lam Yiu; Tsz Lam Yiu; Yujia Wang; Yujia Wang; Yujia Wang; Yujia Wang; Lu Feng; Lu Feng; et al. (Frontiers in Physiology, 2022)
Background: Loss of skeletal muscle mass and function is one of the major musculoskeletal health problems in the aging population. Recent studies have demonstrated differential proteomic profiles at different fetal stages, which might be associated with muscle growth and development. We hypothesized that extract derived from fetal muscle tissues at the stage of hypertrophy could ameliorate the loss of muscle mass and strength in aged mice.Methods: To allow sufficient raw materials for investigation, skeletal muscle extract from fetal sheep at week 16 of gestation and maternal tissue were used in the present study. iTRAQ (isobaric tags for relative and absolute quantitation) and KEGG pathway analyses identified differentially expressed proteins in fetal sheep muscle extract vs. adult sheep muscle extract. Effects of FSME and ASME on human myoblast proliferation were studied. To examine the effect of FSME in vivo, C57BL/6 male mice at 20 months of age were subjected to intramuscular administration of FSME or vehicle control for 8 weeks. A grip strength test and ex vivo muscle force frequency test were conducted. Finally, serum samples were collected for multiplex analysis to determine potential changes in immunological cytokines upon FSME injection.Results: Compared with ASME, 697 and 412 peptides were upregulated and downregulated, respectively, in FSME, as indicated by iTRAQ analysis. These peptides were highly related to muscle development, function, and differentiation from GO enrichment analysis. FSME promoted cell proliferation of myoblast cells (+300%, p < 0.01) without causing significant cytotoxicity at the tested concentration range compared with ASME. After 8 weeks of FSME treatment, the percentage of lean mass (+10%, p < 0.05), grip strength (+50%, p < 0.01), and ability in fatigue resistance were significantly higher than those of the control group. Isometric forces stimulated by different frequencies were higher in the control group. Histologically, the control group showed a larger cross-sectional area (+20%, p < 0.01) than the FSME group. The multiplex assay indicated that FSME treatment did not lead to an elevated circulatory level of inflammatory cytokines. Of note, after FSME treatment, we observed a significant drop in the circulating level of IL-12 (p40) from 90.8 ± 48.3 pg/ml to 82.65 ± 4.4 pg/ml, G-CSF from 23476 ± 8341.9 pg/ml to 28.35 ± 24.2 pg/ml, KC from 97.09 ± 21.2 pg/ml to 29.2 ± 7.2 pg/ml, and RANTES from 325.4 ± 17.3 pg/ml to 49.96 ± 32.1 pg/ml.Conclusion: This is the first study demonstrating the beneficial effect of fetal muscle extract on muscle health in aged mice. Further analysis of the active ingredients of the extract will shed light on the development of a novel treatment for sarcopenia.